Efektivitas Pelayanan Pembuatan Surat Izin Mengemudi (SIM) Menuju Era Digitalisasi di Kepolisian Resor Jayapura Kota - Lina Andayani; Peliman Ndibau; Sahriani Sahriani; Syamsudin Syamsudin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Public service is a fundamental manifestation of the state apparatus function in serving the community. Amid digital transformation, the Police must provide faster, more accessible, and transparent services. This study analyzes the effectiveness of driver's license (SIM) issuance services at the Jayapura City Resort Police (Polresta), focusing on the Digital Korlantas Polri application (SINAR/SIM Nasional Presisi). Rapid growth in vehicle ownership has heightened demand for SIM services, amid persistent illicit practices such as "SIM sistem tembak." Using a qualitative descriptive method, primary data were collected through in-depth interviews with eight purposively selected informants (four Satlantas officers and four community members) and two weeks of participatory observation. Secondary data were drawn from official police documents, Government Regulation No. 76/2020 on Non-Tax State Revenue (PNBP), and relevant literature. Data were analyzed using Miles and Huberman's interactive model, with credibility secured through triangulation. Effectiveness was evaluated across four indicators: (1) effectiveness and efficiency; (2) clarity and certainty; (3) simplicity; and (4) openness. Results reveal that face-to-face procedures were adequate and aligned with PNBP regulations, though SOP implementation was inconsistent across officers. Fee information was posted, but proactive outreach was limited. Procedures were deemed simple, though first-time applicants needed guidance on the SINAR application. Most critically, three of four community informants had never heard of SINAR before visiting the service counter, indicating a gap in digital outreach. These findings contribute evidence on the challenges of digital policy implementation at the sub-national periphery and recommend multi-channel socialization and capacity-building for personnel.